2023
DOI: 10.3390/children10030599
|View full text |Cite
|
Sign up to set email alerts
|

Does Problematic Use of Social Network Mediate the Association between Bullying Victimization and Loneliness among Lebanese Adolescents?

Abstract: (1) Background: Bullying victimization has been associated with several behavioral outcomes, particularly loneliness. Similarly, an increase in social network use has been identified in recent years, particularly during the COVID-19 pandemic, and has been shown to be associated with bullying and loneliness. Investigating the mediating factors of loneliness among bullied adolescents is useful for taking preventive measures in the Lebanese population. This study aims to examine the association between bullying v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…First, bullying victimization significantly predicted a feeling of loneliness. This finding confirms the results of the previous research [40,41], and supports the study's first hypothesis, which states that bullying victimization significantly predicts loneliness. Second, the study further revealed that the feeling of loneliness significantly predicted suicidal behavior.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, bullying victimization significantly predicted a feeling of loneliness. This finding confirms the results of the previous research [40,41], and supports the study's first hypothesis, which states that bullying victimization significantly predicts loneliness. Second, the study further revealed that the feeling of loneliness significantly predicted suicidal behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, researchers have documented a positive association between bullying victimization and loneliness [40,41]. Nevertheless, no researcher has attempted an investigation on the topic in Ghana.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, with the widespread use of mobile phones and the internet, a recent phenomenon known as cyberbullying victimization is also prevalent among adolescents. 18 , 27 It is worth noting that bullying victimization has major detrimental impacts on adolescents’ physical and mental health that are associated with a series of behavioral and emotional problems including depression, 28 anxiety, 29 loneliness, 30 low self-esteem, 31 even suicidal ideation, 32 etc. The affect-regulation model of NSSI states that NSSI is a maladaptive coping style to deal with adverse emotions caused by the experiences of victimization.…”
Section: Introductionmentioning
confidence: 99%